Breakthrough pain in cancer - Hilgier, Maciej (Contemporary Oncology/Współczesna Onkologia, 2007)
Breakthrough pain is defined brief flare up of severe pain that occurs even while the patient is regularly taking pain meducation. Breakthrough pain is relatively common among cancer patients (affects over 50% of patients), particularly those with moderate to severe background pain. Breakthrough pain is one of the most difficult pain syndromes to treat. Breakthrough cancer pain can result from the cancer or cancer treatment, or it may occur during certain activity (e.g. walking, dressing, coughing). It also can occur unexpecte dly, without a preceding incident or clear cause. Persistent and breakthrough pain are distinct components of cancer pain and require separate management. Breakthrough pain is treated with a supplemental short-acting opioid used “as needed” (oral transmucosal fentanyl being the most interesting). Increasing the dose of around-the clock medication to cover all episodes of breakthrough pain is one option, but often leads to over-sedation. One must consider also paracetamol and NSAIDs as rescue medication. Although breakthrough pain is usually managed with supplemental analgesic medication, other means of treatment should be considered such as primary antineoplstic therapies, orthotic devices, neural blocks and thermolesions, etc.